Bacteroides thetaiotaomicron enhances oxidative stress tolerance through rhamnose-dependent mechanisms - Xie, Shuo; Ma, Junze; Lu, Zheng (Frontiers in Microbiology, 2024)
This study probes into the unique metabolic responses of Bacteroides thetaiotaomicron (B. thetaiotaomicron), a key player in the gut microbiota, when it metabolizes rhamnose rather than typical carbohydrates. Known for its predominant role in the Bacteroidetes phylum, B. thetaiotaomicron efficiently breaks down poly- and mono-saccharides into beneficial short-chain fatty acids (SCFAs), crucial for both host health and microbial ecology balance. Our research focused on how this bacterium’s SCFA production differ when utilizing various monosaccharides, with an emphasis on the oxidative stress responses triggered by rhamnose consumption. Notably, rhamnose use results in unique metabolic byproducts, including substantial quantities of 1,2-propanediol, which differs significantly from those produced during glucose metabolism. Our research reveals that rhamnose consumption is associated with a reduction in reactive oxygen species (ROS), signifying improved resistance to oxidative stress compared to other sugars. This effect is attributed to specific gene expressions within the rhamnose metabolic pathway. Notably, overexpression of the rhamnose metabolism regulator RhaR in B. thetaiotaomicron enhances its survival in oxygen-rich conditions by reducing hydrogen peroxide production. This reduction is linked to decreased expression of pyruvate:ferredoxin oxidoreductase (PFOR). In contrast, experiments with a rhaR-deficient strain demonstrated that the absence of RhaR causes B. thetaiotaomicron cells growing on rhamnose to produce ROS at rates comparable to cells grown on glucose, therefore, losing their advantage in oxidative resistance. Concurrently, the expression of PFOR is no longer suppressed. These results indicate that when B. thetaiotaomicron is cultured in a rhamnose-based medium, RhaR can restrain the expression of PFOR. Although PFOR is not a primary contributor to intracellular ROS production, its sufficient inhibition does reduce ROS levels to certain extent, consequently improving the bacterium’s resistance to oxidative stress. It highlights the metabolic flexibility and robustness of microbes in handling diverse metabolic challenges and oxidative stress in gut niches through the consumption of alternative carbohydrates.